The Spanish crisis from a Minskyan perspective: A new episode of financial fragility. Issue 3 (3rd July 2019) - Ruiz, Juan Rafael; Cristian, Oana Andreea
Abstract: In this article, we study the development of the financial crisis in Spain from a Minskyan perspective. In the first part we present the theoretical framework based on Minsky and Kindleberger's work where regulatory failures, financial innovation, and great optimism during the growth stage are key to explain the increased financial fragility. We then use the stages proposed by Kindleberger to show that the same ones can be identified and analyzed for the Spanish crisis, where the critical events have unfolded following a Minskyan approach, from the full capacity of the agents to meet payment obligations to their gradual inability of doing so. As this happened, the balance sheets interconnectedness of agents in the economy untied a severe contagion effect throughout the entire economy. We also document a variety of political shifts and regulatory mismanagement issues, both prior and after the crisis, with a significant impact on the evolution of the Spanish financial crisis.